Combined use of ionophore and virginiamycin for finishing Nellore steers fed high concentrate diets (Scientia Agricola, 2013)
Zebu cattle fed high concentrate diets may present inconsistent performance due to the occurrence of metabolic disorders, like acidosis. The isolated use of ionophores and virginiamycin in high grain diets can improve animal performance and reduce the incidence of such disorders, but recent studies suggested that their combination may have an additive effect. Thus, 72 Nellore steers, 389 ± 15 kg initial body weight (BW), were confined and fed for 79 days to evaluate the combination of virginiamycin and salinomycin on performance and carcass traits. Animals were allocated to a randomized complete block design by BW, in a 2 × 2 factorial arrangement of treatments, with two concentrate levels (73 and 91 %) and two virginiamycin levels (0 and 15 mg kg-1), and salinomycin (13 mg kg-1) included in all diets. The interaction was not significant (p > 0.05). Dry matter intake (DMI), average daily gain (ADG), gain-to-feed ratio (G:F), starch consumed, and fecal starch content were higher (p < 0.05) for the 91 % concentrate treatment. These animals also had higher (p < 0.05) hot carcass weight and dressing percentage. Virginiamycin-treated animals showed lower DMI, but ADG and G:F did not differ (p > 0.05) between treatments. Starch consumed and estimated dietary net energy for maintenance (NEm) and gain (NEg) were higher (p < 0.05) for virginiamycin-treated animals, with no substantial effects on carcass traits. The inclusion of virginiamycin in finishing diets containing salinomycin reduced DMI while maintaining ADG and improving NEm and NEg, suggesting an additive effect of virginiamycin and ionophores, but without affecting carcass quality.